Too cold for warm glow? Christmas-season effects in charitable giving - Stephan Müller; Holger A. Rau (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2017)
This paper analyzes seasonal effects and their potential drivers in charitable giving. We analyze whether donations differ between the pre-Christmas shopping season and summer. Our experiment aims to minimize confounding factors and controls for donor heterogeneity. We find that prosocial subjects significantly reduce donations by almost one half in the pre-Christmas shopping season. We identify stress and savings as significant drivers of this result. First, the higher subjects' reported stress level in the Christmas season relative to the rest of the year, the lower donations. Second, the higher relative savings, the lower giving. The findings provide managerial insights for the timing and design of fundraising campaigns.
Keywords: C91; D64; 330; Charitable Giving; Experiment; Seasonal Effects